2013
DOI: 10.1039/c2ta00887d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of nitrogen-doped graphene hydrogels by hydrothermal route with urea as reducing-doping agents

Abstract: Nitrogen-doped graphene hydrogels (NGHs) were synthesized through a one-pot hydrothermal route with graphene oxide (GO) as raw material and urea as reducing-doping agents. The morphology, structure, and components of the NGHs were characterized by scanning electron microscopy, Raman spectroscopy, X-ray diffraction, X-ray photoelectron spectroscopy, methylene blue adsorption, thermogravimetric analysis and electrical conductivity measurements. The results demonstrated that nitrogen was doped into the graphene p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
193
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 363 publications
(204 citation statements)
references
References 36 publications
(47 reference statements)
10
193
1
Order By: Relevance
“…Previous studies showed that the decomposition of N precursors could contribute to the formation of N dopants [ 11b ] and the substitution of carbon atoms with graphitic nitrogen could cause n-type doping, resulting in the down-shift of the G band. [ 17 ] The above results provide an evidence for the incorporation of N atoms into RGO. The chemical structure of the N-doped Fe/Fe 3 C@C/RGO was further studied by infrared spectroscopy (IR).…”
mentioning
confidence: 67%
“…Previous studies showed that the decomposition of N precursors could contribute to the formation of N dopants [ 11b ] and the substitution of carbon atoms with graphitic nitrogen could cause n-type doping, resulting in the down-shift of the G band. [ 17 ] The above results provide an evidence for the incorporation of N atoms into RGO. The chemical structure of the N-doped Fe/Fe 3 C@C/RGO was further studied by infrared spectroscopy (IR).…”
mentioning
confidence: 67%
“…3a. The peaks at 284.5 eV and 532.8 eV correspond to the C1s and O1s signals, respectively [21]. The O1s peak increased in intensity after E-beam irradiation in an aqueous solution, as shown in Table 3.…”
Section: Effects Of E-beam On the Chemical Composition Of Acfs In Difmentioning
confidence: 71%
“…The N1s spectrum of MnS/NG-9 nanocomposite could be tted with two peaks at a binding energy of 398.5 and 400.1 eV corresponding to pyridinic nitrogen and pyrrolic nitrogen atoms in graphene. 36 The strong intensity peaks suggests a good level of nitrogen doping in graphene. The presence of pyrrolic and pyridinic nitrogen in graphene can increase the electrochemical activity of graphene in electrochemical process.…”
Section: View Article Onlinementioning
confidence: 99%